Prey–predator dynamics in seahorses (Hippocampus guttulatus): deciphering fatty acid clues. Issue 4 (30th December 2011) - Faleiro, Filipa; Narciso, Luís
Abstract Understanding the flow of fatty acids between trophic levels can provide important clues on prey–predator dynamics and nutritional requirements of the species. This study investigates the fatty acid flow between enrichment emulsions, Artemia nauplii and Hippocampus guttulatus juveniles, and evaluates the nutritional value of enriched and unenriched Artemia for newborn seahorses. The fatty acid profile of Artemia and seahorses generally reflected the dietary composition, but fatty acids were not linearly transferred between trophic levels. The incorporation of dietary fatty acids showed to be a more complex process involving dietary composition, predator metabolism and nutritional requirements. Artemia composition resulted from a dynamic balance between what was assimilated and metabolized by the nauplii during enrichment. Prey fatty acids were incorporated in seahorses, but HUFA, particularly DHA, were selectively retained to fulfil their high requirements. H. guttulatus newborns were not successfully reared on Artemia nauplii, not even on enriched Artemia, with low survival rates (15.0–26.7%) being observed in all feeding treatments. The high MUFA content and low DHA level of Artemia did not fulfil the high SFA and PUFA requirements of newborn juveniles, particularly their great DHA demands. Higher survivorship was obtained with enriched Artemia, but no differences were detected in juvenile growth.